The impact of climate change on the balanced-growth-equivalent: An application of FUND - David Anthoff; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
The Stern Review added balanced growth equivalences (BGE) to the economic climate change research agenda. We first propose rigorous definitions of the BGE for multiple regions and under uncertainty. We show that the change in the BGE is independent of the assumed scenario of per capita income. For comparable welfare economic assumptions as the Stern Review, we calculate lower changes in BGE between a business as usual scenario and one without climate impacts with the model FUND than the Stern Review found with the model PAGE. We find that optimal mitigation policies give even lower changes in BGE and argue that those policy choices should be the focus of the research effort rather than total damage estimates. Sensitivity analyses show that the Stern Review chose parameters that imply high impact estimates. However, for regionally disaggregated welfare functions, we find changes in BGE that are orders of magnitude higher than the results from the Stern Review, both for total damage as for optimal policy analysis. With regional disaggregation and high risk aversion, fat tails and with that very high welfare losses emerge.
Keywords: 330; Impacts of climate change; balanced growth equivalent; Stern Review; Klimaveränderung; Statistische Methode; Volkswirtschaftlicher Schaden; Soziale Kosten; Welt